Adjusting the british triage system for dental care in South Korean correctional institutions: a cross-sectional study - Ilkwang Hwang; YoungHa Song; Hee-Kyung Park (BMC, 2023)
Abstract Background The oral health status of inmates in South Korean correctional institutions is poor, mainly due to limited resources and an unestablished triage system. Hence, this study aimed to develop a newly structured dental triage system for South Korean correctional institutions, using the British triage system as a reference. Methods This study included 32 public health dentists working at correctional institutions in South Korea in 2020, accounting for the entire population of public health dentists that year. Data on the dentists' evaluation of resources and perceptions of dental service items were collected using a self-administered online survey including 19 dental service items from the British triage system to assess the level of agreement on dental triage items. All responses were recorded within 1 week of request, and a hierarchical cluster analysis was performed to develop a new dental triage system. Results The survey included 31 respondents working at 47 correctional institutions; 16, 14, and one respondent provided dental services at one, two, and three institutions, respectively. Among the correctional institutions, 2%, 74%, and 23% were the National Forensic Hospital, prisons, and detention centres, respectively. The hierarchical cluster analysis identified four adjusted dental triage categories: emergency, urgent, routine, and checkups, mainly in accordance with those in the British system, but a few items were reallocated. The new dental triage system was compared to the existing system and found to have higher specificity and sensitivity, indicating that it may be more effective at meeting the oral health needs of inmates in South Korean correctional institutions. Conclusions This study developed a newly structured dental triage system by adjusting the British system and evaluated its efficacy compared to the existing system. The new system may help improve the oral health status of inmates in South Korean correctional institutions by providing a more organized approach to dental care provision.